OSGi 플랫폼에서 서비스 인젝션 공격 및 대응책 - 김인태(In-Tae Kim); 정경용(Kyung-Yong Chung); 임기욱(Kee-Wook Rim); 이정현(Jung-Hyun Lee) (한국콘텐츠학회 논문지, 10(8), 2010)
The OSGi platform is a Java-based component platform that is being widely used from environments for the application development to enterprise software. The OSGi platform provides dynamic and transparent installation for open environments. However, it open new attacks so that many researches try to solve OSGi vulnerability. Security flaws in OSGi platform are categorized two parts: the JVM and the OSGi platform itself. We focus on vulnerability by OSGi platform itself, particularly service injection. We identify the service injection attack and suggest secure mechanisms to prevent the attack. Those mechanisms are implemented, providing a few modification to the Knopflerfish OSGi implementation and are evaluated through comparing with existing mechanisms. OSGi 플랫폼은 자바 기반의 컴포넌트 플랫폼으로써 애플리케이션 개발 환경에서부터 엔터프라이즈 소프트웨어까지 다양한 분야에 사용되고 있다. OSGi 플랫폼은 개방형 소프트웨어 환경에서 컴포넌트를 동적으로 설치하고 갱신하기 위한 기능을 제공한다. 그러나 이러한 환경으로 인해 새로운 보안상 취약점이 발생하고 있으며 최근 보안문제를 해결하기 위한 연구들이 이루어지고 있다. OSGi 플랫폼에서 취약점은 자바의 멀티 애플리케이션 플랫폼의 한계로 인한 취약점과 OSGi 플랫폼 자체의 취약점으로 분류할 수 있다. 우리는 OSGi 플랫폼 자체의 취약점 중에서 서비스 인젝션에 관한 취약점을 식별하고 이를 방어할 수 있는 매커니즘을 제안한다. 또한 오픈 소스중 하나인 Knopflerfish를 이용하여 제안된 매커니즘을 구현하고 다른 오픈소스들과 비교 평가한다.